SOCIO-PSYCHOLOGY ASPECT IN AN ALTERNATIVE REGULATION FOR CONTROLLING THE UNDERAGED MARRIAGE - Harahap, Kasmudin; Matondang, Saiful Anwar (International Journal of Psychosocial Rehabilitation, 2020)
This research sought an alternative regulation of underaged married. The sociopsychology aspect of married law concerning with; first is seeking the sociopsychology aspect which related to marriage law that fails to control the rising of marriage among the youth; second is is to find a new alternative regulation for underage married problems in some parts of Indonesia. The research used the constructivism paradigm to find the data of problems of youth marriage, analyze case, and to offer a new alternative solution of underage marriage. A legal fact was analyzed with the multi disciplinary contexts. It was applied to a socio-cultural factors of the under aged married issue. Data found that the regulation on the age limit of marriage needs to be revised and reviewed, by revising article 7 paragraph 1 which states 19 years for men and 16 years for women to be 17 years for men and 15 years for women, and there is no need for dispensation against this as mentioned in article 7 paragraph 2 and 3. The offered solution to reduce the age of marriage aims to eliminate the obscurity of the interpretation of the minimum age for marriage, both in positive law, customary law and Islamic law. This study concludes that the constructive paradigm to create a new regulation for reaching the better socio- psychology of newly couples. The regulation of the age of marriage should be changed for a problem resolve of the complexity of legal problems that arise, both for individuals and society, and the state in a broad sense.